De-westernization and Reorientation in Communication: An Appraisal - Acharya, Trishna (Bodhi: An Interdisciplinary Journal, 2024)
This article presents an appraisal on de-westernization and reorientation in the context of communication discipline by employing the message- or artifact-oriented research approach. In this course, de-westernization has been observed as a critical response to Western or Eurocentric discursive paradigm that has been dominant in the academia since the institutionalization of the discipline. This article acknowledges the instrumental role of de-westernization for opening avenues to explore communication from diverse perspectives, and assesses the concept of Asiacentricity as an academic endeavor to bring Asian perspective to the center while theorizing Asian communication practices. The final section of the article presents an appraisal to Adhikary’s Sadharanikaran Model of Communication (SMC) as an example of reorientation incommunication theorization.